Interarticulator coordination in children with and without cerebral palsy. (2nd January 2017) - Nip, Ignatius S. B.
Abstract: The current study investigates how interarticulator coordination changes across speaking tasks varying in articulatory and linguistic demands for children with CP and their typically-developing peers. Articulatory movements from 12 children with spastic CP (7M, 5F, 4–15 years of age) and 12 typically-developing age- and sex-matched peers were cross-correlated to determine the degree of spatial and temporal coupling between the upper lip and jaw, lower lip and jaw, and upper and lower lips. Spatial and temporal coupling were also correlated with intelligibility. Results indicated that children with CP have reduced spatial coupling between the upper and lower lips and reduced temporal coupling between all articulators as compared to their typically-developing peers. For all participants, sentences were produced with the greatest degree of interarticulator coordination when compared to the diadochokinetic and syllable repetition tasks. Measures of interarticulator coordination were correlated with intelligibility for the speakers with CP.